PARTISIPASI ANGGOTA REMAJA 1000 KOMUNITAS DALAM KEGIATAN AKSI SOSIAL DI KOTA BAGANSIAPIAPI KECAMATAN BANGKO KABUPATEN ROKAN HILIR - Arifina, Adruni; Maemunaty, Titi; ', Widiastuti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to determine the participation of adolescents "1000 communities" in social action activities in Bagansiapiapi District Bangko District Rokan Hilir Regency. The formulation of the problem in this research is how high the participation of youth member "1000 Community" in social action activity in Bagansiapiapi City, Bangko Sub-district, Rokan Hilir Regency. After this research is done, it is expected to provide benefits to increase knowledge regarding matters relating to the participation of youth members of "1000 Community" in social action activities, especially for researchers. This study will benefit all groups as knowledge and understanding related to the participation of adolescent members This research is descriptive with quantitative approach which aims to describe the result of research with numbers. The sampling technique used simple sample random sampling technique (simple random sampling). Technique of data retrieval in this research is by technique of inquiry, which amounts to 82 item statement. Data were obtained from 20 respondents for sample and 37 samples for research sample. After the questionnaire was piloted, 4 items were invalid, and the researcher removed all of the invalid statement items. The result of data analysis shows that the participation of adolescent member in social action activity is very high with average percentage score 90,59%. This means that adolescent members of "1000 Community" have a very high level of participation. In view of all aspects and can also be concluded that the most dominant is the goal to be achieved.Keywords: Participation, social action activities